Risks and Impacts of Chromium Metals on Human and Ecosystem Health - Putra, Adewirli; Arman, Eliza; Fitri, Wiya Elsa; Mayaserli, Dyna Putri; Putra, Arief Yandra; Febria, Fuji Astuti (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2024)
This article discusses the harmful effects of chromium metal on human health and the environment. This review aims to provide an in-depth understanding of its negative implications. Analysis of relevant studies provides a comprehensive picture of how Cr (VI) exposure seriously impacts human health and threatens environmental safety. This review method was conducted by identifying and selecting relevant sources through the scientific journal databases PubMed, Google Scholar, and ScienceDirect with the keywords